Merancang Masa Depan: Menyusun Kalender Kehidupan Siswa SMAS Pulau Barranglompo - Mustika Kusuma Basir; St Salmah Sharon (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Workshop on Designing the Future: Creating a Life Calendar for Students of SMAS Pulau Barranglompo aims to increase students' awareness and ability to plan for the future in facing life's challenges and determining their life goals from an early age. The scope of this community service activity includes strengthening self-planning literacy, time management, and the development of students' personal vision and mission. The methods used include interactive material delivery, group discussions, and hands-on practice in compiling life calendars based on self-reflection and short-term and long-term goals. The results of the activity show that students demonstrate an increased understanding of the importance of life planning and are able to compile life calendars that reflect their potential, interests, and future hopes. New facts identified were the lack of personal planning habits among coastal students and their high enthusiasm for visual and narrative approaches in developing life plans. The main conclusion of this activity was that empowerment through a life planning approach was able to foster students' motivation, direction, and personal responsibility in undergoing the education process and living a more focused life. This activity makes a real contribution to building the capacity of students as the next generation with a long-term vision for life.